##
More on the Area Problem.

We have seen that the area of the region under the graph of a
positive function *f* (*x*) on [*a*, *b*] is given by the definite
integral
*f* (*x*) d*x*. The above properties
may help extend this result. Indeed, consider the region
bounded above by the graph of *f* (*x*) and below by the
graph of *g*(*x*), and bounded on the sides by the vertical lines
*x* = *a* and *x* = *b*, with *a* *b*. Of course, we assume that
*g*(*x*) *f* (*x*) for
*x* [*a*, *b*]. Then we have

*Area*(

) =

*f* (

*x*) -

*g*(

*x*)

*dx* .

Note that here we do not assume both functions are positive since
*f* (*x*) - *g*(*x*) is a positive function.

**Remark.** Sometimes you may be asked to find the area of the
region bounded by the graph of two or more functions. The idea
is to split the region into subregions of the type described
above and then use the formula for the subregions.

**Example.** Let us find the area of the region
bounded by the graphs of

*f* (

*x*) =

*x*^{2} and

*g*(

*x*) = 8

.

First let us graph these functions.

Notice that the region is bounded above by *g*(*x*) and below by
*f* (*x*). To find the boundary points which will give the vertical
side lines we need to solve

*f* (

*x*) =

*g*(

*x*) or

*x*^{2} = 8

.

Easily we get *x* = 0 and *x* = 4. So the answer is
We have
**Example.** Find the area of the region bounded by
the three lines

*x* + *y* = 2, *x* - *y* = - 1, and *x* + 2*y* = 2 .

First we graph the three lines to see the region.

Before we proceed with any integration we need to find the points
of intersection of the three lines represented by the functions

*f* (

*x*) = 2 -

*x*,

*g*(

*x*) =

*x* + 1, and

*h*(

*x*) = -

*x* + 1 .

The three points of intersection are **(0,1)**, **(2,0)**, and **(1/2, 3/2)**.
The region may be subdivided into two regions
bounded above by the graph of *g*(*x*) and below by *h*(*x*) with
0 *x* , and bounded
above by the graph of *f* (*x*) and below by *h*(*x*) with
*x* 2.

So

*Area*(

) =

*g*(

*x*) -

*h*(

*x*)

*dx* =

*x* d

*x* =

,

and
*Area*(

) =

*f* (

*x*) -

*h*(

*x*)

*dx* =

1 -

*dx* =

,

which implies
*Area*(

) =

*Area*(

) +

*Area*(

) =

+

=

^{ . }

**
**

**
[Back]
[Next]
**** **
[Trigonometry]
[Calculus]
[Geometry]
[Algebra]
[Differential Equations]
[Complex Variables]
[Matrix Algebra]

S.O.S MATHematics home page
Do you need more help? Please post your question on our
S.O.S. Mathematics CyberBoard.

*Mohamed A. Khamsi *

Helmut Knaust

Copyright © 1999-2017 MathMedics, LLC. All rights reserved.

Contact us

Math Medics, LLC. - P.O. Box 12395 - El Paso TX 79913 - USA

users online during the last hour